Electron‐ and Hydride‐Reservoir Organometallics as Precursors of Catalytically Efficient Transition Metal Nanoparticles in Water. Issue 25 (14th April 2018) - Fu, Fangyu; Wang, Qi; Ciganda, Roberto; Martinez‐Villacorta, Angel M.; Escobar, Ane; Moya, Sergio; Fouquet, Eric; Ruiz, Jaime; Astruc, Didier
Abstract: Nanoparticles (NPs) are actively investigated for their efficient use in catalysis, but their means of synthesis is a key factor influencing their catalytic properties owing to surface coverage with byproducts. Here, neutral electron‐ and hydride‐rich late transition metal organometallics are compared for the synthesis of late transition metal NPs in the presence of poly(vinylpirolidone) (PVP). In particular, the effect of electron‐reservoir donors, hydride‐reservoir donors, and electron‐rich dimers yielding NPs electrostatically stabilized by cationic organometallics are compared in terms of NP size and catalytic efficiency. The catalytic reactions scrutinized with excellent results include 4‐nitrophenol reduction to 4‐aminophenol by NaBH4 for the AuNPs and PdNPs, and Suzuki–Miyaura reactions for the PdNPs. The nature of the reductant has more influence on the NP size in the case of AuNPs than PdNPs, and the best NP catalysts are obtained with hydride‐reservoir complexes as reductants. The less bulky hydride donors are superior, with the complex [CoCp(ŋ 4 ‐C5 H6 )] (Cp=ŋ 5 ‐C5 H5 ) giving the NPs with the best catalyst efficiencies for both reactions. Protection of the NP cores by the organometallic sandwich salt is found to be the key to catalytic efficiency. Abstract : Catalyst design : Redox type and steric parameters control the formation and catalytic activity of metal nanoparticles (see figure). The effect of electron‐reservoir donors, hydride‐reservoir donors, and electron‐rich dimers yielding NPs stabilized by cationic organometallics are compared in terms of NP size and catalytic efficiency. Protection of the nanoparticle cores by the organometallic sandwich salt is found to be important for catalytic efficiency.